PROFESSIONAL TRAINING OF MUSIC AND CHOREOGRAPHY TEACHERS: ARTISTIC-COMMUNICATIVE CONTEXT - Mozgalova, Nataliia; Baranovska, Iryna; Zuziak, Tetiana; Martyniuk, Anna; Luchenko, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The article highlights the importance of artistic communication in the process of professional training of teachers of music and choreography. The purpose of the article is to analyze the artistic and communicative context of professional training of music and choreography teachers. The study used theoretical methods: analysis of psychological and pedagogical literature, synthesis, comparison, generalization of research results; diagnostic methods: interviews, questionnaires, surveys, observations; methods of processing experimental data for quantitative and qualitative analysis of the results of diagnostic studies.The meaning of the concepts is specified: communication, pedagogical communication, communication, artistic communication, artistic-communicative process. The method of introduction of art-communicative context in practice of preparation of teachers of music and choreography is developed, the directions of its realization are defined - art-pedagogical, performing, directing-staging; the levels of interpersonal interaction are highlighted, the communicative, interactive and perceptual aspects of communication are characterized.The results of empirical research have shown that in the process of professional training of teachers of music and choreography, the artistic and communicative context is insufficiently relevant. In individual lessons in instrumental classes and choreography classes, only certain elements are used: information or messages. Innovative technologies and methods of formation of communicative skills and stimulation of artistic communication are offered.Among the innovations of art education are the technology of personification, design technologies, coaching method and start-method of cooperative learning. We are convinced that artistic communication is a powerful and effective means of developing social skills (soft skills), as it allows to involve students in various types of artistic creativity: music, stage, choreography.The study confirmed the importance of activating the artistic and communicative context in the process of professional training of teachers of music and choreography.